Injury incidence, prevalence, and burden in an Argentinian male youth soccer academy: one-season descriptive study - Dominguez, M.; Rico, J. P.; Tedesco, F.; Tondelli, E. (The Physician and Sportsmedicine, 2024)
Objective To prospectively describe the incidence, severity, and burden of injuries in the youth divisions of an Argentinian professional soccer club during a competitive season.